Theoretical geochemistry : applications of quantum mechanics in the earth and mineral sciences - Tossell, John A.; Vaughan, David J., 1946- (Oxford University Press, 1992)
This work is based on the observation that further major advances in geochemistry, particularly in understanding the rules that govern the ways in which elements come together to form minerals and rocks, will require the application of the theories of quantum mechanics. The book therefore outlines this theoretical background and discusses the models used to describe bonding in geochemical systems. It is the first book to describe and critically review the application of quantum mechanical theories to minerals and geochemical systems. The book consolidates valuable findings from chemistry and materials science as well as mineralogy and geochemistry, and the presentation has relevance to professionals in a wide range of disciplines. Experimental techniques are surveyed, but the emphasis is on applying theoretical tools to various groups of minerals: the oxides, silicates, carbonates, borates, and sulfides. Other topics dealt with in depth include structure, stereochemistry, bond strengths and stabilities of minerals, various physical properties, and the overall geochemical distribution of the elements.